Makna Denotasi, Konotasi, dan Mitos dalam Kidung Pepeling Karya Ki Anom Suroto Sebagai Media Pengingat Sholat dalam Pujian Pasca Adzan - Qurrota A’yuna Khaeroni; Alfiah; Nuning Zaidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Da'wah is an activity of voicing, calling, inviting or appealing to someone. In the Islamic religion, da'wah is an activity carried out to invite or distribute information related to the teachings of the Islamic religion. One example of da'wah is by providing information in the form of reminders to pray. Kidung Pepeling is a song initiated by Ki Anom Suroto which contains a warning message for carrying out prayers. This research regarding Kidung Pepeling by Ki Anom Suroto is intended to find out the meaning of connotation, denotation and myth contained in the lyrics. The scalpel used in this research is to use a literary critical approach, namely Roland Barthes' semiotic approach. This research was conducted using a qualitative descriptive method. The data collection process carried out was by collecting the lyric text of the Pepeling song as an initial stage. Then, the text that has been collected is first translated into Indonesian to simplify the research process. After that, the data analysis process in the form of the lyric text of the ballad is carried out based on the meaning, denotative, connotative and mythical meaning contained in the lyrics. The results obtained from this research were the discovery of semiotic signs in the form of deontation meaning, connotation meaning and mythical meaning in the Pepeling song.